2000
DOI: 10.1074/jbc.m002599200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of METH-1/ADAMTS1 Processing Reveals Two Distinct Active Forms

Abstract: METH-1/ADAMTS1 is a member of a newly described family of genes that contain metalloprotease, disintegrin, and thrombospondin-like motifs. We have recently shown that METH-1 protein is a potent inhibitor of angiogenesis. Here, we demonstrate that secreted human pro-METH-1 is processed in two consecutive steps to release both p87 and p65 active forms. The p87 form lacks the N-terminal prodomain and p65 results from an additional processing event in the C-terminal end. Generation of p87 was blocked with specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 41 publications
12
161
0
Order By: Relevance
“…However, other documented forms (79 and 64 kDa) (Vazquez et al, 1999) of ADAMTS-8, which retain antiangiogenic activity after proteolytic cleavage, may be present in normal and tumour brain tissues, would not be detected in the present study. ADAMTS-1 processing resulting in the release of the C-terminal end does not affect the catalytic function of the protease (Rodriguez-Manzaneque et al, 2000), with both processed forms having the ability to block EC proliferation in a dose dependent manner. Moreover, it is suggested that processing might release two fragments with distinct/independent functions in the ECM.…”
Section: Discussionmentioning
confidence: 97%
“…However, other documented forms (79 and 64 kDa) (Vazquez et al, 1999) of ADAMTS-8, which retain antiangiogenic activity after proteolytic cleavage, may be present in normal and tumour brain tissues, would not be detected in the present study. ADAMTS-1 processing resulting in the release of the C-terminal end does not affect the catalytic function of the protease (Rodriguez-Manzaneque et al, 2000), with both processed forms having the ability to block EC proliferation in a dose dependent manner. Moreover, it is suggested that processing might release two fragments with distinct/independent functions in the ECM.…”
Section: Discussionmentioning
confidence: 97%
“…This band probably corresponds to the active, mature enzyme (theoretical molecular mass 78.8 kDa). A band of similar size (p87) has previously been reported for mature ADAMTS-1 [37]. C-Terminal processing of recombinantly expressed ADAMTS-1 has been described previously [37,38].…”
Section: Purification and Characterization Of Rhadamts Enzymesmentioning
confidence: 99%
“…Dysregulation of ADAM and ADAMTS expression has been reported in different types of cancer by RT-PCR profiling and microarray analysis [64][65][66][67]. The picture is rendered complex by the existence of different isoforms resulting from alternative splicing described in ADAM-8, -9, -10, -11, -12, -15, -19, -22, -28, -29, -30 and -33 or ADAMTS-4 and TS-6 genes [36,50,51,[68][69][70][71][72][73][74][75][76][77] or from putative post-translational modulations [23] resulting from a processing of the molecule by the metalloproteinase domain itself [78] or by other MMPs [79].…”
Section: Implication Of Adams and Adamtss In Physiology And Pathologymentioning
confidence: 99%